EFISIENSI EKONOMI USAHATANI KANGKUNG (Ipomea reptans Poir) DI KELURAHAN GUNTUNG PAYUNG KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Yan Yozef Agus Suratman; Achmad Syaripiadi Santosa (Chlorophyl, 2021)
This research aims are: (1). Knowing the technical description of kale farming carried out by farmers; (2) knowing the costs, revenues, and benefits of kale farming; (3) knowing the economic efficiency of kale farming in Guntung Payung Village, Landasan Ulin Sub-district, Banjarbaru City. This research uses survey method with observation technique. The sampling method uses a simple random sampling. The population of farmers who cultivate kale is 112 people, then 25% of the total farmers in this village, 28 farmers are used as respondent farmers. The result of the research is that the average land area used by farmers is 0.13 hectares (2.46 wholesale) and the status of land ownership is property rights. The production an average of kale farming in Guntung Payung Village was 4,035.71 bunches/farmer or 31,043.92 bunches/hectare (1,018.93 kg/farmer or 7,83793ton/hectare = 7,837.93 kg/hectare). The average cost is IDR 928,021.49/farmer, the average revenue is IDR 4,075.720/farmer and the average profit is IDR 3,147,698.51/farmer. The economic efficiency or feasibility of kale farming in Guntung Payung Village is 3.68. This economic efficiency or R/C greater than 1 means that it is profitable for kale farming